DAMPs are able to skew CD4+ T cell subsets and increase the inflammatory profile in pregnant women with preeclampsia - Romao-Veiga, Mariana [UNESP] (2022)
Preeclampsia (PE) is characterized by abnormal activation of the immune system. The intense systemic inflammatory reaction, could be related to the presence of molecules released after cell stress or death, that are capable of inducing inflammation and are known as damage-associated molecular patterns (DAMP). This study evaluated the profile of T cells through the analysis of transcription factors and the cytokines produced after culture with or without DAMPs: heat shock protein 70 (Hsp70), hyaluronan (HA) and monosodium urate (MSU). Twenty pregnant women with PE, 20 normotensive (NT) pregnant women and 20 non-pregnant (NP) women were studied. The results showed polarization toward Th1/Th17 and a decrease in Th2/Treg profiles in preeclamptic women associated with elevated levels of TNF, IFN-γ, and IL-17A and diminished levels of TGF-β1 and IL-10 when compared to the normotensive group. In addition, preeclamptic women had a higher percentage of cells co-expressing T-bet/GATA-3 and T-bet/RORγt and fewer T-bet/FoxP3 cells when compared to normotensive group. MSU induced an increase in IFN-γ and IL-22 in all studied groups. MSU, HA, and Hsp70 induced significant higher production of TNF in the PE and NP groups. The PE group showed elevated levels of TGF-β1 after incubation with MSU, HA, and Hsp70, whereas HA and Hsp70 decreased TGF-β1 production in NT group. The results suggest that these alarmins may play a role in the activation of innate and adaptive immune systems by skewing CD4 + T cells and increasing the release of inflammatory cytokines, thereby contributing to the pathogenesis of this important syndrome.